Antioxidant system gene polymorphism and restenosis risk after coronary stenting - Yu. A. Shuvalova; A. N. Meshkov; A. I. Kaminny; A. N. Samko; R. O. Shirokov; D. V. Stambolsky; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика)
Aim. To study the links between four polymorphisms of three antioxidant enzymes (catalase, paraoxonase, endothelial NO synthase) and restenosis risk after coronary artery stenting (CAS).Material and methods. The study included male patients with coronary heart disease (CHD), stable angina and angiographically verified stenosis of one or two main CA ≥70%, after intracoronary CAS with non-eluting stents and control coronary angiography 6 months later. Angiographical stenosis was determined as local reduction in CA diameter ≥50%. In all participants, -262 C/T polymorphism of CAT gene, L55M and Q192R polymorphisms of PON gene, and E298D polymorphism of eNOS gene were identified.Results. The study included 101 patients, and restenosis was diagnosed in 44%. E298D polymorphism of eNOS gene was associated with stent restenosis. In D allele carriers, restenosis risk was higher (p=0,008). The combination of LM/QQ genotypes for L55M and Q192R polymorphisms of PON gene was twice as prevalent in restenosis  group: 41% vs. 21% (p=0,044).Conclusion. Genotyping on E298D polymorphism of eNOS gene and L55M and Q192R polymorphisms of PON gene could be used for post-CAS restenosis risk stratification in Russian patients.